English Major Students' Perceptions of Dialogue Practice in Improving Vocabulary Mastery at Universitas Negeri Semarang - Dewanti Mira Ardani; Christianti Tri Hapsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine students' perception of the use of dialogue practice in vocabulary learning in the English Education Study Program. This study uses a qualitative descriptive research design with participants selected through purposive sampling techniques. Data was collected through questionnaires and semi-structured interviews. Questionnaire data was analyzed using descriptive statistics, while interview data was analyzed qualitatively to support and explain quantitative findings. The results of the study showed that students had a positive perception of the use of dialogue practice as a vocabulary learning strategy. Most students agree that dialogue practice increases motivation, interest, and positive attitudes in vocabulary learning because it allows for the direct use of new vocabulary in meaningful communication. In terms of implementation in the classroom, dialogue practice is perceived as an interactive and collaborative activity with clear learning objectives. However, some students still feel initial discomfort in using new vocabulary for fear of making mistakes, although these feelings diminish as the intensity of the practice increases. Regarding vocabulary knowledge, dialogue practice helps students understand vocabulary contextually, including pronunciation, word meaning, and the appropriate use of vocabulary in sentences. Dialogue practice is perceived as an effective approach in vocabulary learning because it integrates cognitive, affective, and social aspects in language learning. This study recommends the application of dialogue practice in English learning as an effort to improve vocabulary mastery and active language use. Keywords: Dialogue Practice, EFL Learning, Vocabulary Learning, Student Perception, Vocabulary Mastery